The estimation of effect of combined influence of pollutants on plants - Z. M. Alieva (Юг России: экология, развитие)
There was carry aut the estimate of ability of application the law of fermentative kinetics to the plants on the eksample of redish in this article. The deflection of theoretical forecasting the death rapid of sprout getting during the experiment is 7.9 %. It shows the ability of such method of approach in eslimating of the influense of toxic substances on to the plants.